Permeability Evolution of Fractured Rock Subjected to Cyclic Axial Load Conditions - Zilong Zhou (Geofluids, 2020)
Permeability experiments on saw-cut fractured rock subjected to cyclic axial load conditions were conducted on the MTS815 rock mechanics testing system. The influence of the frequency and amplitude of cyclic axial forces on axial displacement and permeability evolution of fractured rock was experimentally investigated. Results show that the increasing frequency under the same amplitude of axial load leads to a reduction in axial displacement, but a drop followed by an increase in permeability, while the permeability values oscillated sharply under high amplitude of cyclic loads, which can be attributed to the production of gouge materials. Besides, the increase in axial displacement roughly contributed to the permeability reduction, and excessive amplitude of cyclic load posed limited boost to the permeability enhancement. By comparing with the quasistatic function, we found that it did not completely correspond to the trend of the permeability evolution subjected to cyclic axial forces, and sensitivity coefficients evolving with frequency and amplitude should be considered. A new function of the permeability evolution subjected to the amplitude and frequency of cyclic axial forces was derived and verified by the experimental data. This study suggests that small amplitude and high frequency of dynamic forces have the potential for enhancing the permeability of fracture and triggering the disaster of fractured rock.